Addressing the Validity of a Teacher Made-Test Constructed by High School English MGMP Teachers in West Lombok - Bahrul Hadi; Untung Waluyo; Henny Soepriyanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
In second language learning, assessment plays a vital role in evaluating and measuring students’ proficiency levels based on the material taught. Therefore, this research aims to examine the strategies, practices, and challenges faced by an English MGMP teacher in West Lombok face during the development of a valid teacher-made test for Senior High School students. This study employs a qualitative design, and the data were collected through triangulation techniques such as teacher interviews and document analysis of the test item from two schools in West Lombok, six teachers from SMAN 1 Narmada, and four teachers from SMAN 1 Gerung. The findings indicate that the majority of teachers maintain the content validity by utilizing the curriculum, module, and test blueprint as their core references before and during the test development process. However, several test items were found to be misaligned with the curriculum and the materials taught. Furthermore, none of the respondents considered the alignment between the test with the specific language skills that being assessed. In addition, the majority of the problem that teacher usually face is the wide variation in students’ proficiency levels, which makes it difficult to design a fair test for all students. The study concludes that, although the most of English teachers had ensured the content validity of their test items by referring to official documents such as the curriculum, teaching modules, and test blueprints during the test development process, there are several items which still deviated from the material taught, and none of teachers addressed whether the test formats appropriately matched the language skills being assessed such as speaking, writing, listening and reading. Their strategies mainly involved adjusting items to students’ proficiency levels, collaborating with colleagues, and managing test banks through digital platforms such as WhatsApp and the PIJAR application. However, none reported using analytical measures like item discrimination index to examine test quality. The primary obstacle they faced was the broad variation in students’ abilities, alongside many learners performing below the expected standard. This challenge was intensified by the absence of recent professional development initiatives or coordination from the English MGMP in West Lombok over the last one to two years.